Aflatoxin management strategies in sub-Saharan Africa - Falade, Titilayo D.O. (IntechOpen, 2018)
Aflatoxins are natural poisons produced by some members of the Aspergillus section Flavi group. Their control is critical in sub-Saharan Africa as in other parts of the world because of the health and economic dangers that aflatoxins cause. Aflatoxin management requires a pipeline approach (from production to consumption) that addresses the pre-disposing factors to aflatoxin contamination. These strategies will involve strategies at the pre-harvest, peri-harvest and post-harvest stages to prevent contamination. Post-contamination practices are also relevant in situations where avoidance of contamination is not possible. Strategies that inform producers, handlers, consumers of what aflatoxins are, how they can be prevented from contaminating produce or managed are important for aflatoxin management. Additionally, the engagement public and private sectors, regional bodies and community associations are critical for effective aflatoxin management as they have the capacity to influence behavior changes and modulate practices that predispose food and feed to aflatoxin contamination. Furthermore, the role of research and academic institutions to provide factual information and effectively communicate technical information for aflatoxin management is crucial to avoid misinformation and application of improper practices.